1991
DOI: 10.1002/ana.410300604
|View full text |Cite
|
Sign up to set email alerts
|

Excitotoxicity in the embryonic chick spinal cord

Abstract: Recent evidence implicates excitatory amino acids (EAAs), acting as excitotoxic agents, in the pathogenesis of neurological disorders involving the spinal cord. In this study, we used the chick embryo spinal cord as an in vitro model for studying the sensitivity of spinal neurons to the excitotoxic effects of EAA agonists. Compounds tested include the prototypic receptor-specific agonists, N-methyl-D-aspartate (NMDA), quisqualic acid (Quis), and kainic acid (KA), and the plant-derived excitotoxic food poisons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 48 publications
(11 reference statements)
3
22
0
Order By: Relevance
“…1 and 2). Similar morphological changes have been reported using a number of different in vivo and in vitro models (Ikonomidou et al, 1996;Nag and Riopelle, 1990;Stewart et al, 1991). These findings suggest that a direct toxicity mediated by the NMDA receptor is an unlikely mechanism for the pathogenesis of ALS or other motor neuron diseases.…”
Section: Relevance To Alssupporting
confidence: 71%
See 2 more Smart Citations
“…1 and 2). Similar morphological changes have been reported using a number of different in vivo and in vitro models (Ikonomidou et al, 1996;Nag and Riopelle, 1990;Stewart et al, 1991). These findings suggest that a direct toxicity mediated by the NMDA receptor is an unlikely mechanism for the pathogenesis of ALS or other motor neuron diseases.…”
Section: Relevance To Alssupporting
confidence: 71%
“…Previous studies have demonstrated NMDA toxicity to cortical, hippocampal (Choi, 1987(Choi, , 1988Rothman, 1985) and spinal cord (Ikonomidou et al, 1996;Nag and Riopelle, 1990;Regan et al, 1990;Stewart et al, 1991;Wells et al, 1994) neurons. Our studies provide information on the specific effects of NMDA on spinal cord cholinergic enzymes.…”
Section: Relevance To Alsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, NMDA antagonists were not neuroprotective, and NMDA itself was not toxic to motor neurons. Acute non-NMDA-mediated toxicity affecting motor neurons has been suggested by studies of chicken spinal cord in vitro (26) and neonatal rats in vivo (27). In contrast, our model clearly demonstrates selective non-NMDAmediated slow neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies revealed a major effect on motor neuron (MN) survival or animal life span. [135][136][137] and are more vulnerable than other neuronal subsets to excitoxicity induced by influx of Ca 2+ through GluRs. [138][139][140] Most of the studies investigating the possible implication of GluRs in ALS pathogenesis are therefore particularly focused on ionotropic GluR NMDA and on GluR2 subunit expression and editing, which confer Ca 2+ impermeability to the AMPA/KA GluR.…”
Section: Astrocytementioning
confidence: 99%